Gas-generating nanoparticles for contrast-enhanced ultrasound imaging - Sun, In-Cheol (Nanoscale, 2019)
We present a gas-generating solid nanoparticle as a new concept of the ultrasound contrast agent. The developed nanoparticles are sufficiently small (less than 100 nm in diameter) to escape vasculature and yet, upon external pulsed laser light activation, release nitrogen gas for the enhanced contrast in ultrasound imaging. The gas-generating nanoconstructs combine the photocatalytic function of gold nanoparticles and photolysis of azide compounds. Using ultrasound imaging, we demonstrate the controlled, on-demand generation of nitrogen gas from nanoparticles due to the decomposition of azide groups trigggered by pulsed laser irradiation. The resulting gas forms bubbles that cause backscattered ultrasound signals and, therefore, modulate the contrast in ultrasound imaging.